The Property (Relationship) Amendment Act 2001: A Conceptual Change - Peart, Nicola (Victoria University of Wellington Law Review, 2008)
When the Matrimonial Property Act 1976 was introduced, Tony Angelo and Bill Atkin analysed the Act in conceptual terms and welcomed the change from a purely separate property regime to a community property system. It steered an acceptable middle course between competing demands. The Act operated as a deferred community property regime on separation, which was relatively simple and predictable for most couples. This paper analyses the changes made by the Property (Relationships) Amendment Act 2001 and concludes that it has changed the conceptual basis of the property sharing regime, but not in a coherent or principled manner. While the community property system is strenghened in some respects, it is weakened in other respects and overall it introduces an undesirable level of uncertainty and unpredictability.